2014
DOI: 10.1007/s11032-014-0065-8
|View full text |Cite
|
Sign up to set email alerts
|

Genetic factors responsible for eating and cooking qualities of rice grains in a recombinant inbred population of an inter-subspecific cross

Abstract: The eating and cooking qualities of rice grains are the major determinants of consumer preference and, consequently, the economic value of a specific rice variety. These two qualities are largely determined by the physicochemical properties of the starch, i.e. the starch composition, of the rice grain. In our study, we determined the genetic factors responsible for the physicochemical properties of starch in recombinant inbred lines (RILs) of japonica cv. Tainung 78 × indica cv. Taichung Sen 17 (TCS 17) cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 50 publications
2
50
1
4
Order By: Relevance
“…For instance, in the present study, no significant correlation between PT and SBV was observed in both IG (-0.07) and HG (-0.05), which was consistent with the findings of Xu et al [18] where r was 0.10. Although a significant positive correlation between PT and SBV was observed in the studies by Wang et al [17] and Hsu et al [15], r was very small at only 0.18 and 0.23, respectively. The weak correlation between PT and SBV indicates that maybe no apparent physicochemical relationship exists between them, so that the correlation coefficient between them was inconsistent across different studies.…”
Section: Discussionmentioning
confidence: 86%
“…For instance, in the present study, no significant correlation between PT and SBV was observed in both IG (-0.07) and HG (-0.05), which was consistent with the findings of Xu et al [18] where r was 0.10. Although a significant positive correlation between PT and SBV was observed in the studies by Wang et al [17] and Hsu et al [15], r was very small at only 0.18 and 0.23, respectively. The weak correlation between PT and SBV indicates that maybe no apparent physicochemical relationship exists between them, so that the correlation coefficient between them was inconsistent across different studies.…”
Section: Discussionmentioning
confidence: 86%
“…This analysis shows that majority of the candidate genes that have previously been reported to be involved in amylose synthesis do not seem to be associated with amylose synthesis in the system under study. This finding is consistent with results of many studies which have reported that the effect of various starch related genes and their interaction depends on genetic background as well as environmental factors (Hsu et al 2014). The only locus that has consistently been stable across genetic backgrounds is the waxy locus which encodes GBSS1, indicating that it is a major effect locus involved in amylose biosynthesis (Mikami et al 2008;Septiningsih et al 2003;Tan et al 1999;Zhou et al 2003).…”
Section: Association Analysis Identifies Known and Novel Candidate Gesupporting
confidence: 89%
“…Determination of the ECQ traits is imperative given that it influences the multiple uses of rice at both industrial and domestic scale [19]. Genetic background and environmental interactions cause a variation in ECQs of different germplasms [20].…”
Section: Discussionmentioning
confidence: 99%